Epistemic justice, mindfulness, and the environmental humanities : reflections on teaching - Adsit, Janelle (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Epistemic Justice, Mindfulness, and the Environmental Humanities explores how contemplative pedagogies and mindfulness can be used in the classroom to address epistemic and environmental injustice. In recent years there has been a groundswell of interest in contemplative pedagogies in higher education, with increasing attention from the environmental sciences, environmental humanities, and sustainability studies. Teachers and writers have demonstrated how mindfulness practices can be key to anti-oppression and anti-racist efforts, both in and out of the classroom. Not all forms of contemplative pedagogy are suited for this anti-colonial and anti-oppressive resistance, however. Simply adopting mindfulness practices in the classroom is not enough to dislodge and dismantle white supremacy in higher education. Epistemic Justice, Mindfulness, and the Environmental Humanities advocates for mindfulness practices that affirm multiple epistemologies and cultural traditions. Written for educators in the environmental humanities and other related disciplines, the chapters interrogate the western uptake of mindfulness practices and suggest anti-colonial and anti-oppressive methods for bringing mindfulness into the classroom. The chapters also discuss what mindfulness practices have to offer to the pursuit of a culturally relevant pedagogy for the diverse students who come to institutions of higher education in the Anglophone world. This highly applied and practical text will be an insightful read for educators in the environmental humanities and across the liberal arts disciplines"--
Pluriversality & multiepistemic humility -- What is epistemic justice? -- Staying with the practice: the resources of mindfulness -- Reading and writing practices in the classroom -- Gathering together -- No final word.
Keywords: Human ecology and the humanities; Environmental justice; Mindfulness (Psychology); Culturally relevant pedagogy; EDUCATION / Higher; EDUCATION / Teaching Methods & Materials / Arts & Humanities; NATURE / Ecology